Political Strategic Management in China –Lessons from Tesco - Fan, Di (2015)
With the development of global economy, it was noticed that currently many multinational companies have implemented different business strategies in abroad markets to achieve more business resources, economic scale and thus enhance their competitiveness. Many empirical studies claimed that, during companies expanding their business as a strategy of internationalization, a key strategy – political strategy is quite helpful in a regulated market to assist companies achieve financial benefits. However, regard to political strategic management, many research works took advantage of data from countries with low institutional constraints as sample, and could not find clear relationships between every element under the framework. In order to draw a complete map of political strategic management, this dissertation will utilize the case of Tesco in Chinese market, examining the “Political Capabilities”, “Political Resources” they have held, and “Political Strategies” they have implemented. We finally found that, to achieve financial benefits and political advantages in countries with high institutional constraints, a powerful “Political Capability” should be held by companies. As a consequence, companies have to increase their “Political Resources” accordingly and thus enjoy dynamic “Political Strategies” to launch.